2017
DOI: 10.1111/apa.13932
|View full text |Cite
|
Sign up to set email alerts
|

Using a spontaneous profile rather than stimulation test makes the KIGS idiopathic growth hormone deficiency model more accessible for clinicians

Abstract: We validated the KIGS IGHD prediction model and found that the stimulated GH peak can be reliably replaced by the GH 12h with similar accuracy. This makes the model more accessible for clinicians, who can then provide realistic expectations for the growth response during the first year of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
(39 reference statements)
0
8
0
Order By: Relevance
“…Since 1920, when EVANS first demonstrated that the growth-promoting substance in the pituitary gland is growth hormone, scholars have studied the GH gene extensively and intensively, and have achieved important results [35] . It has been reported that growth hormone (GH) is able to combine with the HRE sequence of the β-casein gene to promote receptor activation and synergistically increase the specific expression of lactoproteins [25,36] .…”
Section: Discussionmentioning
confidence: 99%
“…Since 1920, when EVANS first demonstrated that the growth-promoting substance in the pituitary gland is growth hormone, scholars have studied the GH gene extensively and intensively, and have achieved important results [35] . It has been reported that growth hormone (GH) is able to combine with the HRE sequence of the β-casein gene to promote receptor activation and synergistically increase the specific expression of lactoproteins [25,36] .…”
Section: Discussionmentioning
confidence: 99%
“…IGFBP3 is the main carrier of IGF-1 in blood circulation and can prolong the half-life of IGF-1 in blood circulation. IGF-1 can promote the proliferation of bone cells, increase bone length, participate in the regulation of protein metabolism, induce vitamin D activation (Duchén et al 2017). IGFBP3 plays a role in hypoxia-induced angiogenesis (Granata et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…All prepubertal children with height below −2 SDS or more than 1.5 SDS below mid‐parental height (MPH) without obvious signs of syndrome were examined with a spontaneous GH profile, 13 and considered for GH treatment based on the prediction according to the model mentioned above.…”
Section: Methodsmentioning
confidence: 99%